KEBERLANJUTAN SUMBER DAYA IKAN BUTINI (GLOSSOGOBIUS MATANENSIS) BERDASARKAN DIMENSI KELEMBAGAAN DI DANAU TOWUTI - Djuko, Dwiayu Juliati; Satary, Dewi Yanuarita; Nadiarti, Nadiarti (Gorontalo Fisheries Journal, 2024)
Butini fish resources are endemic fish that must be sustainably managed in an ecosystem where butini fish require an integrated management plan involving all stakeholders. This study aims to 1) determine the sustainability status of butini fish resources based on the institutional dimension; 2) and determine the sensitive attributes in the institutional dimension of butini fisheries, the research was conducted in Lake Towuti, South Sulawesi Province, during January-March 2023. Data collection was done by field survey method. The institutional dimension was analyzed with Rappid Appraisal for Fisheries Sustainability (RapFISH) analysis to determine management strategies. The results showed that the sustainability status of butini fish resources in Lake Towuti for the institutional dimension is in the good enough category. The sensitive attribute in the institutional dimension is stakeholder participation with a leverage value of 8.78 while the fisheries management plan is 8.71.